Design of emotional branding communication model based on system dynamics in social media environment and its influence on new product sales - Zhang, Yin; Tu, Zhongfang; Zhao, Wenting; He, Lu (Frontiers in Psychology, 2022)
In the current social media environment, brand emotional marketing communication has become a common marketing tool for brand owners. It is particularly important and urgent to study the emotional marketing communication in the social media environment. Based on the perspective of brand equity theory, combined with the new characteristics of marketing communication in the social media environment, this paper constructs a brand emotional marketing communication model in the social media environment. In order to arouse and arouse the emotional needs of consumers and induce the resonance of consumers' hearts, this paper uses the system dynamics (SD) method to simulate and analyze the new product marketing system. This paper discusses the asymmetric news communication of different brands of the same commodity under the effect of this view exchange mechanism, that is, only the initially weak brands in the market adopt marketing methods, while the strong brands do not participate in social marketing activities. It is found that the influence of marketing frequency and marketing intensity on symmetric communication and asymmetric communication is different. In the face of different types of competitors, the marketing strategy of weak brands should be emphasized. Through the unit consistency test, structure verification test, effectiveness and rationality test, it is proved that the brand emotional marketing communication model and new product sales interaction simulation model established in this paper are reasonable and effective.